2017
DOI: 10.1016/j.kjms.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive cryosurgery in patients with bone metastatic prostate cancer: A retrospective analysis

Abstract: The current study is a retrospective analysis of 49 patients with bone metastatic prostate cancer: 26 receiving androgen deprivation therapy (ADT) alone versus 23 receiving cytoreductive cryosurgery of the primary tumor plus ADT treatment. Progression-free survival (PFS) was the primary outcome variable, and Cox proportional hazards regression analysis was used to identify predictors for PFS. The baseline characteristics were generally comparable between the 2 groups. Median follow-up time was 41 months (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…The primary treatment methods of PCa are surgery, radiotherapy, cryosurgery, chemotherapy and endocrinotherapy. However, the effects of these treatments are not satisfactory, with the 5-year survival rate of patients with distant metastasis in the United States remaining ~20% ( 4 , 6 - 8 ). Therefore, it is necessary to identify a safe and effective strategy for treating PCa.…”
Section: Introductionmentioning
confidence: 99%
“…The primary treatment methods of PCa are surgery, radiotherapy, cryosurgery, chemotherapy and endocrinotherapy. However, the effects of these treatments are not satisfactory, with the 5-year survival rate of patients with distant metastasis in the United States remaining ~20% ( 4 , 6 - 8 ). Therefore, it is necessary to identify a safe and effective strategy for treating PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Cryotherapy was used for treatment of the primary tumor in our trial based on anecdotal and preclinical evidence, which identified it as potentially producing the most profound local immune response 14,15 . Though reported in a retrospective series, this is the first report of cytoreductive cryoablation in a clinical trial setting 34 . Patients in our study tolerated cryoablation well with all patients being treated in an outpatient setting, no grade 3 adverse events were observed, and low rates of urinary side effects ensued.…”
Section: Discussionmentioning
confidence: 84%
“…The experimental group was treated with 6 articles of radical prostatectomy, 1 article of robot-assisted radical prostatectomy, 2 articles of cytoreductive prostatectomy, and 1 article of prostate cancer cryosurgery; the control group (without local treatment) only received endocrine therapy. HR and 95% confidence interval data were directly obtained from three articles [ 23 , 26 , 28 ], and the remaining seven articles [ 20 22 , 24 , 25 , 27 , 29 ] were obtained by extracting survival rate from Kaplan-Meier curve in the literature, and then converted by EXCEL program designed by Tierney et al [ 17 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%